2019
DOI: 10.1080/14786435.2019.1569767
|View full text |Cite
|
Sign up to set email alerts
|

A constitutive model coupling irradiation with two-phase lithiation for lithium-ion battery electrodes

Abstract: When lithium-ion batteries serve in extreme environments like space, severe irradiation might induce significant decay of the electrochemical performances and mechanical properties. In this paper, an electrochemical-irradiated constitutive model is proposed to explore the evolution of dislocation, defect and stress in electrodes during a twophase lithiation process. The results from the analytic formulation and finite difference calculations show that, as Li intercalation proceeding, the hoop stress in the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 78 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…All of these unwanted phenomena become even more serious when LMBs are operating under abuse conditions, i.e., high/low temperature, high current density, and overcharging. Especially, these topics are of importance since they can directly affect the safety of our lives [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…All of these unwanted phenomena become even more serious when LMBs are operating under abuse conditions, i.e., high/low temperature, high current density, and overcharging. Especially, these topics are of importance since they can directly affect the safety of our lives [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initial mechanics studies employed linear elasticity and linear fracture mechanics , for capturing the stresses developed in anode particles experiencing volume expansions over 300%. Since then, computational simulations have been widely used to model the stress generation, anisotropic volume expansions, and fracture of Si by using chemo-mechanical models implemented in the finite element method, , phased field modeling, and atomistic simulation . Chemomechanical finite element modeling showed that hollow amorohousSiNPs (a-SiNPs) have a lower stress-induced barrier of lithiation than solid a-SiNPs .…”
Section: Introductionmentioning
confidence: 99%
“…However, there was little work that investigated the micromorphology, optical, and electrical properties of ZnS:(Cu, Al) phosphors after high‐dose electron radiation. The combination of simulation and experiment is a suitable method to analyze the effect of radioactive particles on materials 28,29 . It is meaningful for exploring the performance changes and micromechanism of energy conversion section after radiation in batteries, providing important guideline for predicting battery service behavior.…”
Section: Introductionmentioning
confidence: 99%